An English Teacher’s Perception on Students’ Difficulties in Pronunciation - Kalsum, Lutfiah; Tahir, Muhammad; G., Hasriani (State University of Makassar, 2024)
This research aims to determine teachers’ perception on students’ difficulties in pronunciation. The researcher used a qualitative approach and conducted with a semi-structure interview for this research. The data resource in this research was an English teacher that teach grade 7,8, and 9 SMP Sanur Makassar. It was obtained from interview with 9 questions and the English teacher as the respondent. The result of the research concluded that: teachers perceive that on average students have low pronunciation skills, this is influenced by the fact that English is a different language from students' everyday language, students' lack of self-confidence, and students believe that English is the most difficult language. With this challenge, teachers overcome it by giving students motivation, giving students pronunciation practice with friends or groups so that students can be directly involved in activities to improve pronunciation skills. In addition, teachers provide media such as videos and songs in English, so that students can imitate the correct pronunciation of native speakers. The media used by the teacher have a positive impact on the students' pronunciation. difficulties in pronunciation of English can be caused by interference from the student's first language. In addition, in the context of English learning, teachers who understand students' difficulties in understanding and pronouncing sounds can influence the teaching methods they apply. This shows that teachers' perceptions of students' pronunciation abilities can influence the learning approaches they use. Assessing students' pronunciation skills is an important aspect of language education. Furthermore, research has shown that teachers' observations and interactions with students on a daily basis can provide reliable information about students' pronunciation abilities and students demonstrated varying levels of improvement in their pronunciation when speaking English. In conclusion, the data collected by the researcher and the findings are influence of teachers' perceptions on their learning approaches and emphasize the importance of understanding students' pronunciation abilities. This highlights the need for effective pronunciation instruction and assessment methods in language education.Keywords: Teachers’ Perception, Pronunciation.